Underutilization of Angiotensin Converting Enzyme Inhibitors among Heart Failure Patients - Lean, Q.Y.; Shamsuddin, N.; Wan Ahmad, W.A. (2008)
There are well established guidelines regarding the use of Angiotensin converting enzyme inhibitors (ACEI) in the management of heart failure (HF). In spite of that, many studies has documented underutilization of ACEI. Thus, this retrospective observational study aimed to evaluate the utilization of ACEI, to identify the pattern of ACEI use and the factors that might contribute to underutilization of ACEI. The target population was hospitalized HF patients in University Malaya Medical Centre (UMMC). Of 321 hospitalized HF patients, only 57% of them were treated with ACEI. 51.2% of the patients treated with ACEI received low dose (≤ 25% from target dose) at discharge. Factors that have significant association with the underutilization of ACEI included serum potassium with creatinine, chronic renal failure and other concurrent medications used (frusemide, aspirin, potassium chloride, calcium channel blockers and angiotensin receptor blockers). The findings indicated that the utilization of ACEI in the management of HF in UMMC is considerably low.